2014
DOI: 10.1002/jsfa.6782
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the rheological properties of wheat dough during short‐term storage of wheat

Abstract: It was shown that small deformation dynamic oscillation and large deformation creep-recovery tests can be successfully employed to monitor the changes in flour quality during wheat storage and that required storage period after wheat harvesting has to be defined according to wheat variety initial rheological properties and its gluten quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…The gradual decrease in the phase angle was observed in the dehulled γ‐irradiated millet samples (DHI1 and DHI2.50 kGy) on day 90 (Figure 1c,d). Similarly, a study highlighted decrease in elasticity of the wheat samples during storage (Hadnađev et al., 2015), which could be related to the change in phase angle. Moreover, the findings failed to report the perfect trend for phase angle among the dehulled and whole millet samples (Figure 1c,d).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The gradual decrease in the phase angle was observed in the dehulled γ‐irradiated millet samples (DHI1 and DHI2.50 kGy) on day 90 (Figure 1c,d). Similarly, a study highlighted decrease in elasticity of the wheat samples during storage (Hadnađev et al., 2015), which could be related to the change in phase angle. Moreover, the findings failed to report the perfect trend for phase angle among the dehulled and whole millet samples (Figure 1c,d).…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, these properties are related to the millet growing areas and storage conditions. During the storage, the pasting and rheological behavior may change due to starch and protein composition (Hadnađev et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the endosperm absorbs less water and the number of grains decreases considerably, affecting its productivity. On the other hand, MC above of the permitted, which is 13% for wheat, directly influences the rheological properties of wheat (BRASIL, 2010;HADNAĐEV et al, 2015). Therefore, all samples evaluated are under the limits predicted by law, despite the positive correlation between MC and the percentage the brusone in the grain.…”
Section: 1-analysis In Grains Resultsmentioning
confidence: 99%
“…Hence, the wheat flour dough falls under the non‐Newtonian fluid category. Several mathematical tools (e.g., Bingham, Hershal–Bulkley and Casson models) are available for modeling the rheological data and estimating yield stress, viscosity and viscous stress parameters . Changes in the physiochemical properties such as lipid content, carbohydrate content, protein content and lipoxygen activity of wheat grains with prolonged storage have been studied .…”
Section: Introductionmentioning
confidence: 99%
“…Empirical and fundamental rheological tests were used to differentiate between wheat flours harvested in different years and it was observed that the flour strength was highest for control wheat flour and decreased from the wheat flour of 2005 to 2004 . Rheological changes with respect to the short‐term storage of wheat grains were studied and the results indicated that the intensity of rheological changes in dough during wheat storage might be dependent on gluten quality . The fundamental viscoelastic tests performed on wheat dough are the force deformation ratio test, creep test, dynamic test and the stress‐relaxation test .…”
Section: Introductionmentioning
confidence: 99%